2023
DOI: 10.3389/fpubh.2023.1136031
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of COVID-19 pandemic and associated factors among college and university students in Ethiopia: a systematic review and meta-analysis, 2022

Abstract: BackgroundThe Corona virus disease 19 (COVID-19) pandemic is a human tragedy that occurred in this era. It poses an unprecedented psychological, social, economic, and health crisis. The mental health and well-being of entire societies are suffering as a result of this crisis, but the suffering is greater in students at all levels of education and must be addressed immediately. Thus, this study was aimed to estimate the pooled prevalence and associated factors of the psychological impact of COVID-19 among highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This study was lower than the systematic review in Saudi Arabia with an estimated pooled prevalence of depression of 51.5%, 78 and the systematic review and meta-analysis done in Pakistan, which was 42.66%. 79 It is also lower than different studies conducted in Ethiopia 43.49%, 80 Hong Kong 68.5%, 27 India 43.7%, 28 Pakistan 40.9% 29 and Saudi Arabia 43%. 30 The possible reason for the discrepancy might be due to differences in sample size, sampled study participants and sociocultural level.…”
Section: Discussionmentioning
confidence: 69%
“…This study was lower than the systematic review in Saudi Arabia with an estimated pooled prevalence of depression of 51.5%, 78 and the systematic review and meta-analysis done in Pakistan, which was 42.66%. 79 It is also lower than different studies conducted in Ethiopia 43.49%, 80 Hong Kong 68.5%, 27 India 43.7%, 28 Pakistan 40.9% 29 and Saudi Arabia 43%. 30 The possible reason for the discrepancy might be due to differences in sample size, sampled study participants and sociocultural level.…”
Section: Discussionmentioning
confidence: 69%
“…In other words, medical illness among students was indicated as a significant predictor of anxiety. Hence, the literature similarly reported that the existence of illnesses, whether medical or mental illnesses, was a contributing factor leading to anxiety as well as psychological distress among university students [ 52 , 53 , 54 ]. Therefore, we recommend the application of medical screening of students to screen for the presence of illnesses that might hinder students’ academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has touched every aspect of human life worldwide, impacting business, research, education, health, economy, sports, transportation, worship, social interactions, politics, governance, and entertainment ( 7 , 8 ). This influence affects patients, healthcare workers, communities, and students, spanning all populations ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%